Stimuli-responsive nanogel composites and their application in nanomedicine. (1st June 2015) - Molina, Maria; Asadian-Birjand, Mazdak; Balach, Juan; Bergueiro, Julian; Miceli, Enrico; Calderón, Marcelo
Abstract : We highlight the description of stimuli responsive nanogels in the form of composites and their application in nanomedicine. Abstract : Nanogels are nanosized crosslinked polymer networks capable of absorbing large quantities of water. Specifically, smart nanogels are interesting because of their ability to respond to biomedically relevant changes like pH, temperature, etc. In the last few decades, hybrid nanogels or composites have been developed to overcome the ever increasing demand for new materials in this field. In this context, a hybrid refers to nanogels combined with different polymers and/or with nanoparticles such as plasmonic, magnetic, and carbonaceous nanoparticles, among others. Research activities are focused nowadays on using multifunctional hybrid nanogels in nanomedicine, not only as drug carriers but also as imaging and theranostic agents. In this review, we will describe nanogels, particularly in the form of composites or hybrids applied in nanomedicine.